Predicting the redox properties of uranyl complexes using electronic structure calculations. Issue 12 (7th March 2017) - Khungar, Bharti; Roy, Ankita; Kumar, Anand; Sadhu, Biswajit; Sundararajan, Mahesh
Abstract : A plethora of chemical reactions is redox driven processes. The conversion of toxic and highly soluble U(VI) complexes to nontoxic and insoluble U(IV) form are carried out through proton coupled electron transfer by iron containing cytochromes and mineral surfaces such as machinawite. This redox process takes place through the formation of U(V) species which is unstable and immediately undergo the disproportionation reaction. Thus, theoretical methods are extremely useful to understand the reduction process of U(VI) to U(V) species. We here have carried out the structures and reduction properties of several U(VI) to U(V) complexes using a variety of electronic structure methods. Due to the lack of experimental ionization energies for uranyl (UO2 (V)‐UO2 (VI)) couple, we have benchmarked the current and popularly used density functionals and cost effective ab initio methods against the experimental electron detachment energies of [UO2 F4 ] 1‐/2‐ and [UO2 Cl4 ] 1‐/2‐ . We find that electron detachment energy of U(VI) predicted by RI‐MP2 level on the BP86 geometries correlate nicely with the experimental and CCSD(T) data. Based on our benchmark studies, we have predicted the structures and electron detachment energies of U(V) to U(VI) species for a series of uranium complexes at the RI‐MP2//BP86 level which are experimentally inaccessible till date. We find that the redox active molecular orbital is ligand centered for the oxidation of U(VI) species, where it is metal centered (primarily f‐orbital) for the oxidation of U(V) species. Finally, we have also calculated the detachment energies of a known uranyl [UO2 ] 1+ complex whose X‐ray crystal structures of both oxidation states are available. The large bulky nature of the ligand stabilizing the uncommon U(V) species which cannot be routinely studied by present day CCSD(T) methods as the system size are more than 20–30 atoms. The success of our efficient computational strategy can be experimentally verified in the near future for the complex as the structures are stable in gas phase which can undergo oxidation. Abstract : A cost‐effective RI‐MP2 method can be used as a very accurate predictive tool to study the redox properties of uranyl complexes. Ligand‐based ionization is noted for U(VI) species, whereas metal‐based ionization is observed for U(V) species. Within the density functional theory framework, it is found that the M06‐2X functional can be employed as a computationally cheaper alternative to the RI‐MP2 approach.